Inklusivitas Pelayanan Publik di Era Digital: Analisis Aksesibilitas Layanan Adminduk dari Perspektif Gender dan Strata Pendidikan - Muhammad Asril Arilaha,; Hadi, Muksin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Digital transformation in public services frequently encounters inclusivity challenges for specific community groups. This study aims to analyze the inclusivity of population administration services in the digital era based on gender and educational strata perspectives in Ternate City. A mixed-methods approach with a concurrent embedded design was employed, involving 525 respondents selected through accidental sampling. The research instrument utilized a 4-point Likert scale to measure nine standard service elements. The results indicate that the Public Satisfaction Index (IKM) reached 90.67, categorized as "Excellent". Although gender accessibility was found to be egalitarian, a significant performance asymmetry exists between the integrity dimension (score of 3.98) and technical infrastructure reliability (score of 3.48). Furthermore, groups with lower educational backgrounds still face digital literacy barriers (digital divide). This study concludes that successful digital transformation requires a reconciliation between technological advancement and humanistic values through hybrid approaches and technical assistance to ensure equitable access for vulnerable groups